Selected NDT techniques in heat treatment control - Beneš, Petr; Vítovec, Vilém (Manufacturing Technology Journal, 2021)
The quality of machine parts is determined not only by the quality of the materials themselves, but also by their heat treatment, which also includes frequently used chemical-thermal processes, such as case-hardening, leading to an increase in the mechanical properties of the surface layers of the material. Heat treatment involves thermal diffusion processes, which are quite complex and therefore there is always a certain probability that the desired material state will not be created. It is therefore desirable to have control methods, preferably of a non-destructive nature, which can detect imperfections and thus prevent future damage that could occur in this way. The paper deals with the use of commonly used non-destructive material testing techniques such as eddy currents, ultrasonic control and acoustic emission method to verify the correctness of thermal and case-hardening processing of steels.